ANALYSIS OF THE USE OF INTERACTIVE LEARNING MEDIA IN IMPROVING LEARNING MOTIVATION IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SMK 2 MEI BANDAR LAMPUNG - Trajaya Trajaya; Baharudin Baharudin; Agus Susanti (Jurnal Bilqolam Pendidikan Islam, 2026)
The limited variety of learning media used in Islamic Religious Education often makes the learning process less engaging and impacts student learning motivation. This study aims to analyze the use of interactive learning media in improving student learning motivation in Islamic Religious Education at SMK 2 Mei Bandar Lampung. This study used a qualitative, descriptive approach. Data were collected through observation, interviews, and documentation, involving the principal, Islamic Religious Education teachers, and students as research informants. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that the use of interactive learning media can improve student learning motivation, as indicated by increased attention, active participation, and enthusiasm in learning. These findings indicate that the use of interactive learning media has positive implications for the development of more innovative and effective Islamic Religious Education learning strategies.